Self-harm in children placed in a Court-Mandated Holding and Education Centre: analysis of socio-demographic variables and influence of implementation of judicial measures - G. García (Sociedad Española de Sanidad Penitenciaria, 2015)
Objectives: To analyze and understand the existence of self-harming behavior in a detention centre for minors. Methods: Review of self-harm cases detected in a population of 94 inmates in 2013. Results: 26.5% of young offenders have conducted some form of self injury. 28% of individuals with self harming behaviors have more than 6 episodes over the period of internment. Self-beating is the most common type of self-harm performed by this group. Inmates serving sentences in the therapeutic section tend to present spillover effects in terms of self-injury. Discussion: The population held in prison show higher percentages of self-harm than amongst the general population. The chosen type of behavior is determined by the institution. Inmates that present greater mental fragility tend to perform these behaviors and in greater number.